Empowering Local Communities Through Circular Economy: Transforming Cement Paper Waste into Eco-Friendly Packaging and Handicrafts - Simondinata, Gunawan; Widjaja, Rita; Ciawi, Harry (Edumedia Solution, 2025)
The community surrounding the Indocement factory in Cirebon, particularly women in the assisted villages, faces a lack of skills and limited economic opportunities. Additionally, the factory produces residual paper waste from cement packaging, which is often underutilized. To address these issues, two community engagement initiatives were implemented: (1) crafting eco-friendly